2022
DOI: 10.3390/children9060823
|View full text |Cite
|
Sign up to set email alerts
|

Do Physical Fitness and Executive Function Mediate the Relationship between Physical Activity and Academic Achievement? An Examination Using Structural Equation Modelling

Abstract: Background: Physical activity health benefits are widely known. However, the association between physical activity, physical fitness, executive function, and academic performance need further investigation. Additionally, one of the literature gaps reveals scarce and mixed findings on what mediators of physical activity may affect academic achievement. Purpose: This investigation aims to provide knowledge about the mediation role of physical fitness and executive function in the association of physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…This article also directly pointed out that executive function act as mediators of the association between physical activity and academic achievement 35 . Muntaner MA's finding further provided the evidence that regular physical exercise leads to improvements in physical fitness and may support cognitive skills and academic performance in children aged between 9 and 13 years old 36 . And on this basis, we further demonstrated that the improvement effect of the two exercises together is more significant than that of the single exercise ways.…”
Section: Discussionmentioning
confidence: 94%
“…This article also directly pointed out that executive function act as mediators of the association between physical activity and academic achievement 35 . Muntaner MA's finding further provided the evidence that regular physical exercise leads to improvements in physical fitness and may support cognitive skills and academic performance in children aged between 9 and 13 years old 36 . And on this basis, we further demonstrated that the improvement effect of the two exercises together is more significant than that of the single exercise ways.…”
Section: Discussionmentioning
confidence: 94%
“…Our formal mediation analysis is in line with a 2015 Cochrane review(35), which found no evidence that PA-induced increases in CRF resulted in improved cognitive performance in healthy older adults without known cognitive impairment. More recently, studies in children have observed a mediating effect of fitness on the relationship between PA and executive function(36) and academic attainment(37). However, these studies, in children aged 9-13y, may not be generalisable to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Any movement produced by the contraction of skeletal muscles that causes an increase in energy expenditure beyond the basal level is referred to as physical activity (PA). (Muntaner-Mas et al, 2022;Piggin, 2020). World Health Organization (WHO) (2020) recommends adults aged between 18 and 64 to participate in 75-150 min of moderate to vigorous intensity of physical activity (MVPA) throughout the week.…”
Section: Introductionmentioning
confidence: 99%
“…On top of that, US Department of Health and Human Services (2018) adds that adults should also engage in any muscle-strengthening activities that involve major muscle groups for at least two or more days in their weekly repertoire. Previous studies have been documented the health benefits of physical activity over the life span (Muntaner-Mas et al, 2022), such as reducing risk for non-communicable diseases including type 2 diabetes, hypertension, dyslipidemia, metabolic syndrome, and some cancers (Asigbee et al, 2018;F. W. Booth et al, 2012;Elmagd, 2016).…”
Section: Introductionmentioning
confidence: 99%